1976
DOI: 10.1042/cs0510313
|View full text |Cite
|
Sign up to set email alerts
|

Generation of Ammonia from Non-Urea Sources in a Faecal Incubation System

Abstract: 1. A 25% faecal suspension in sodium chloride solution, incubated anaerobically at 37 degrees C for 48 h, showed excellent survival of all the main groups of faecal bacteria. 2. All faecal incubation systems studied generated large amounts of ammonia, particularly those in which bacterial counts fell during incubation. As normal faeces contain negligible amounts of urea this ammonia must have been generated from sources other than urea. 3. Ammonia was also generated by faeces delivered by sodium chloride enema… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

1979
1979
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 16 publications
0
23
0
Order By: Relevance
“…In vitro incubation systems have been previously validated for the modeling of bacterial metabolism in the rumen (18) and in the human colon (19). Despite inherent limitations such as lack of bicarbonate secretion and absorption of organic acids which occur in vivo, short-term (1 h) incubations as used in the present studies have been shown to reflect accurately the rate of in vivo fermentation reactions (18,20).…”
Section: Discussionmentioning
confidence: 99%
“…In vitro incubation systems have been previously validated for the modeling of bacterial metabolism in the rumen (18) and in the human colon (19). Despite inherent limitations such as lack of bicarbonate secretion and absorption of organic acids which occur in vivo, short-term (1 h) incubations as used in the present studies have been shown to reflect accurately the rate of in vivo fermentation reactions (18,20).…”
Section: Discussionmentioning
confidence: 99%
“…1). Vince et al (1976) showed that bacterial populations in faecal slurries remain substantially unchanged after incubation for 48 h at 37 "C. In order to remove readily utilizable substrates, faecal slurries in the present study were preincubated for 48 h before addition of casein or BSA. The rapid hydrolysis of protein, and the formation of metabolic end products in these slurries, confirmed that gut bacteria can survive and remain metabolically active for extended periods in vitro.…”
Section: Discussionmentioning
confidence: 99%
“…These were isolated as described previously, mainly from the faeces of healthy adult subjects, but some isolates from the terminal ileum were also examined (Hamilton et al, 1970;Vince et al, 1976). Numerically dominant groups of bacteria were selected for testing, and placed in one of the following categories, account being taken of several criteria including, the ability to grow aerobically or anaerobically, gram-staining properties and spore formation: enterobacteria; streptococci; micrococci; Bacillus spp.…”
Section: Bacteriamentioning
confidence: 99%